Brachiaria grass for sustainable livestock production in Rwanda under climate change - Mutimura, Mupenzi; Ghimire, Sita R. (Springer, 2021)
Brachiaria grass is an important tropical forage of African origin. It produces high amount of palatable and nutritious biomass, tolerates abiotic and biotic stresses, improves soil fertility, increases livestock productivity, and reduces adversities of climate change. Since 2007, several improved Brachiaria grass cultivars (Brachiaria brizantha cvs. Marandú, MG4, Piatã, and Xaraés; B. decumbens cv. Basilisk; B. humidicola cvs. Humidicola and Llanero; Brachiaria hybrid cvs. Mulato, Mulato II, and Cayman; and other hybrid lines Bro2/0465, Bro2/1452, and Bro2/1485) have been introduced and evaluated in Rwanda for adaptation, biomass yields, animal nutrition, livestock productivity, and environmental qualities. Both on-farm and on-station evaluations of 13 improved Brachiaria grass cultivars and 2 checks – local Brachiaria grass and buffel grass at two different agroecological zones of Rwanda showed superior adaptation, higher biomass yields, and higher nutritive values of all Brachiaria grass cultivars compared to buffel grass. Subsequent study evaluating the impact of cutting regimes on agronomic and nutritional characteristics of improved Brachiaria cultivars and Napier grass showed forages harvested at 90 days after planting with high crude protein content (between 137 and 167 g/kg DM for Mulato II and Piatã, respectively) and high metabolizable energy (up to 9 MJ/kg DM for Piatã). These attributes have shown to increase animal production optimizing retention time of the particle phase of digesta in dairy cows which was shorter for Piatã (62.8 h) than Napier grass (83.1 h). Piatã had higher voluntary dry matter intake than Napier grass hence increased milk yield up to 50%. Furthermore, heifer fed on Mulato II had up to 54.7% more body weight and less enteric methane (14%) than heifers fed on Napier grass. These studies have shown Brachiaria grass as the most productive forage of high farmer preference due to its adaptation in low rainfall and acidic soils and the production of green foliage year-round. Therefore, improved Brachiaria grass has been promoted in 20 of 30 districts of Rwanda through various livestock development initiatives benefitting more than 4,800 farmers from South, Eastern, and Northern Provinces of Rwanda. In this chapter, we also discussed the prospects of Brachiaria grass in supporting the growing livestock sector in Rwanda and emerging challenges.